Respon Nilai Keadilan Atas Keberlakuan Asas Legalitas Dalam Hukum Pidana - Ari Nurhaqi (LPPM STIH Awang Long, 2022)
The response of the value of justice to the application of the principle of legality is essentially an attempt to make changes to the concept of the Criminal Justice System which is considered retributive and inhumane. The principle of legality with the guarantee of legal certainty does not fully guarantee community justice, therefore a shift in the orientation of thought which was originally only formal legality to material legality is needed.